On Retention of Eventual Stability of Perturbed Impulsive Differential Systems - Anju Sood; Sanjay Kumar Srivastava (Institute for Research and Community Services (LPPM) ITB, 2016)
In this paper, a system of non nonlinear differential equations withimpulse effect at fixed time moments is considered and criteria for retention ofuniform eventual stability of its perturbed impulsive differential systems undervanishing perturbations are established. Sufficient conditions are obtained byusing piecewise continuous Lyapunov functions. An example is also worked outto illustrate the results.AMS Subject Classification: 34CXX, 34DXX, 34A37, 34K45.